2022
DOI: 10.28940/terra.v40i0.990
|View full text |Cite
|
Sign up to set email alerts
|

Ajuste de la Ecuación Universal de Pérdida de Suelo en parcelas de escurrimiento ubicadas en una región del centro de México

Abstract: Debido a la falta de métodos para estimar con precisión la pérdida de suelo en México, es necesario realizar estudios experimentales para estimar la erosión basada en datos validados. Por lo que el objetivo de esta investigación fue estimar la Tasa de Erosión Anual (A) para diversas coberturas de suelo empleando la Ecuación Universal de Pérdida de Suelo (EUPS), y ajustada mediante su relación con el índice de Generación de Sedimentos (IGS) obtenido en lotes de escurrimiento. Los resultados muestran que, durant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Values of factor C have been proposed associated with the thickness of the topsoil in the soils in agroforestry systems (Pérez Nieto et al, 2012). Calibration coefficients for the RUSLE model have also been generated for bare soils, vertical tillage and natural vegetation (Valdivia‐Martínez et al, 2022). Although factor calibration has been identified, there are few ( n = 4) studies found on this subject; additionally, these factors have been identified for specific topographical conditions and production systems, which difficult their application at a regional scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Values of factor C have been proposed associated with the thickness of the topsoil in the soils in agroforestry systems (Pérez Nieto et al, 2012). Calibration coefficients for the RUSLE model have also been generated for bare soils, vertical tillage and natural vegetation (Valdivia‐Martínez et al, 2022). Although factor calibration has been identified, there are few ( n = 4) studies found on this subject; additionally, these factors have been identified for specific topographical conditions and production systems, which difficult their application at a regional scale.…”
Section: Resultsmentioning
confidence: 99%
“…In studies where the USLE family models were used, the erosion factor assessment was defined by the data availability in each case. Studies implemented three principal strategies to calculate the erosivity factor (R); first, the EI30 index proposed by Wischmeier and Smith (1978) to calibrate USLE model at plot (Pérez-Salinas et al, 2019) and watershed (Prado-Hern andez et al, 2017) scale using the minute temporal resolution; second, the Modified Fournier Index (Arnoldus, 1980) at plot (Valdivia-Martínez et al, 2022) and watershed (Pando Moreno et al, 2003) using monthly temporal resolution; third, the isoerosivity study in Mexico, where 14 equations were calibrated to estimate R factor from annual temporal data for each precipitation region (Becerra Moreno, 1999). The erodibility factor is calculated following Wischmeier and Smith (1978), using the information from the soil survey and soil cartographic units.…”
Section: A Brief Description Of the Sew Study In Mexicomentioning
confidence: 99%
“…La estimación de las pérdidas de suelo se puede realizar a través de la modelación del fenómeno (métodos indirectos) usando ecuaciones, como la ecuación universal de pérdida de suelo [USLE], por sus siglas en inglés (Valdivia-Martínez et al, 2022) y por el montaje de unidades experimentales en campo (métodos directos) como las parcelas de escorrentía y simuladores de lluvia (León Peláez, 2001). Estos métodos (directos e indirectos) se han comparado entre sí en diferentes estudios, como las parcelas experimentales y el método USLE (Oyarzun Ortega, 1993) en Chile y en México con el uso de estacas de erosión y la metodología RUSLE [USLE revisada] (Pando Moreno et al, 2012); evidenciando que el uso de las metodologías indirectas sobreestima los valores de erosión hídrica en las regiones estudiadas.…”
Section: Introductionunclassified